PENGGUNAAN VIRTUAL LAB SEBAGAI ALTERNATIF PEMBELAJARAN PRAKTIKUM SISWA SECARA DARING PADA DUA SMK DI KOTA BATAM - Maya Marsevani; Marvin Tandedi; Neilcent Claudio Siuwandy; Annisa Salsabila; Steven Steven; Calvin Yantson; Tiara Puspita Ayuni; Wenny Ong; Aldy Tri Sentanu; Nanda Jala Sena (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
The spread of the COVID-19 pandemic has hampered the implementation of the education system in Indonesia, one of which is the Vocational High School (SMK) education system in Batam City. Students who initially attended classes at school are now forced to attend them online at home. Online classes certainly carry their own challenges. An example that can be taken from the survey results is that there are still schools whose online learning is not supported by a Learning Management System. This research was conducted by distributing surveys to SMK students and students’ parents, as well as interviews with SMK teachers. The result of this research is to create a website to support online learning for schools that still do not have their own Learning Management System. This website is called V-Lab.